2016
DOI: 10.1051/0004-6361/201628077
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of a complex linearly polarized spectrum of Betelgeuse dominated by depolarization of the continuum

Abstract: Context. Betelgeuse is an M supergiant that harbors spots and giant granules at its surface and presents linear polarization of its continuum. Aims. We have previously discovered linear polarization signatures associated with individual lines in the spectra of cool and evolved stars. Here, we investigate whether a similar linearly polarized spectrum exists for Betelgeuse. Methods. We used the spectropolarimeter Narval, combining multiple polarimetric sequences to obtain high signal-to-noise ratio spectra of in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
58
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 27 publications
(71 citation statements)
references
References 44 publications
12
58
1
Order By: Relevance
“…The observed surface structures in this wavelength range are generally consistent with the results from radiative hydrodynamical simulations of convection (Chiavassa et al 2010;Montargès et al 2014). Aurière et al (2016) demonstrated that spectropolarimetry at visible wavelengths makes it possible to detect the presence of hot spots through their depolarization of the continuum spectrum of the star. Using this technique, hot spots have been reported by Tessore et al (2017b) on Betelgeuse at the epoch of the ALMA observations.…”
Section: Nature Of the Continuum Hot Spotsupporting
confidence: 82%
See 1 more Smart Citation
“…The observed surface structures in this wavelength range are generally consistent with the results from radiative hydrodynamical simulations of convection (Chiavassa et al 2010;Montargès et al 2014). Aurière et al (2016) demonstrated that spectropolarimetry at visible wavelengths makes it possible to detect the presence of hot spots through their depolarization of the continuum spectrum of the star. Using this technique, hot spots have been reported by Tessore et al (2017b) on Betelgeuse at the epoch of the ALMA observations.…”
Section: Nature Of the Continuum Hot Spotsupporting
confidence: 82%
“…Several authors have reported the observation of bright spots on the disk of Betelgeuse (Young et al 2000;Haubois et al 2006;Ravi et al 2011;Aurière et al 2016), although their presence is not systematic (Burns et al 1997). Interferometric observations in the near-infrared domain by Montargès et al (2016) and Haubois et al (2009) have shown the presence of temperature inhomogeneities on the infrared photosphere of Betelgeuse.…”
Section: Nature Of the Continuum Hot Spotmentioning
confidence: 98%
“…Thomson) scattering and temporal evolution of hot spots. Extending Clarke and Schwarz's interpretation, Aurière et al (2016) suggested that the linear polarisation observed in the spectral line of Betelgeuse is indeed an effect of the depolarisation of the continuum set to zero. have computed the expected polarisation of the continuum in the 400 -700 nm range due to hot spots.…”
Section: Stellar Pulsationsmentioning
confidence: 82%
“…Harrington & Kuhn (2009b,a) and Lèbre et al (2011) have shown that such a property is often present in the Balmer lines of evolved stars. The existence of linearly polarisation across individual metal lines in absorption has been reported for the Mira star χCygni by Lèbre et al (2014) and for the red supergiant Betelgeuse by Aurière et al (2016). Using the Least Squares Deconvolution (LSD, Donati et al 1997), Tessore et al (2015) found evidence of linear polarisation in the spectral lines of the RV Tau variable R Scuti and Sabin et al (2015) in the lines of the RV Tau variable U Monoceroti as well in the post-AGB star 89 Herculis.…”
Section: Introductionmentioning
confidence: 90%
“…Harrington & Kuhn (, ) and Lèbre et al () have shown that linear polarization is often present in the Balmer lines of evolved stars. Using the least squares deconvolution method (LSD, Donati et al ), linear polarization across metal lines in absorption was detected for the Mira star χ Cygni (Lèbre et al ), for the red supergiant Betelgeuse (Aurière et al ), for the RV Tau variable R Scuti (Tessore et al ), and for the RV Tau variable U Monoceroti as well as for the post‐AGB binary star 89 Herculis (Sabin et al ).…”
Section: Introductionmentioning
confidence: 99%